Detection of enteroviruses in the intestine of type 1 diabetic patients - Oikarinen, M.; Tauriainen, S.; Honkanen, T.; Oikarinen, S.; Vuori, K.; Kaukinen, K.; Rantala, I.; Mäki, M.; Hyöty, H. (Clinical and experimental immunology, 2008)
Summary Enterovirus infections have been diagnosed more frequently in type 1 diabetic patients than in the healthy population, and enteroviruses have also been found in the pancreas of diabetic patients. Primary replication of the virus occurs in the gut, but there are no previous studies evaluating possible presence of virus in the intestine of diabetic patients. The purpose of this study was to investigate if enteroviruses can be found in small intestinal tissue of type 1 diabetic patients. Formalin‐fixed, paraffin‐embedded upper intestinal biopsy samples were analysed for the presence of enterovirus using in situ hybridization and immunohistochemistry. Enterovirus was detected by in situ hybridization in six (50%) of the type 1 diabetic patients (n = 12) but in none of the control subjects (n = 10, P = 0·015). Immunohistochemistry identified enterovirus in nine (75%) of the patients and one (10%) control subject (P = 0·004). The presence of the virus was confirmed by reverse transcription–polymerase chain reaction in one of the four patients from whom a frozen and unfixed sample was available. Intestinal morphology was normal in all study subjects. The results suggest that a substantial proportion of type 1 diabetic patients have an ongoing enterovirus infection in gut mucosa, possibly reflecting persistent enterovirus infection. This observation opens new avenues for further studies on the possible role of enteroviruses in human type 1 diabetes.